Effect of high-intensity interval training versus sprint interval training on time-trial performance: A systematic review and meta-analysis - Rosenblat, M. A.; Perrotta, A. S.; Thomas, S. G. (Sports Medicine, 2020)
Background: Two forms of interval training commonly discussed in the literature are high-intensity interval training (HIIT) and sprint interval training (SIT). HIIT consists of repeated bouts of exercise that occur at a power output or velocity between the second ventilatory threshold and maximal oxygen consumption (VO2max). SIT is performed at a power output or velocity above those associated with VO2max. Objective: The primary objective of this study is to systematically review published randomized and pair-matched trials to determine which mode of interval training, HIIT versus SIT, leads to a greater improvement in TT performance in active and trained individuals. The second objective of this review is to perform a subgroup analysis to determine if there is a distinction between HIIT programs that differ in work-bout duration. Data Sources: SPORTDiscus (1800-present) and Medline with Full Text (1946-present) were used to conduct a systematic literature search. Study Selection: Studies were selected for the review if they met the following criteria: (1) individuals (males and females) who were considered at least moderately trained (~ 3-h per week of activity) as specified by the authors of the included studies; (2) between the ages of 18 and 45 years; (3) randomized or pair-matched trials that included a HIIT and a SIT group; (4) provided detailed information about the interval training program; (5) were at least 2 weeks in duration; (6) included a TT test that required participants to complete a set distance. Results: A total of 6 articles met the inclusion criteria for the subjective and objective analysis. The pooled analysis was based on a random-effects model. There was no difference in the change in TT performance when comparing all HIIT versus SIT (0.9%; 90% CI - 1.2-1.9%, p = 0.18). However, subgroup analysis based on duration of work interval indicated a 2% greater improvement in TT performance following long-HIIT (= 4 min) when compared to SIT. There was no difference in change in VO2max/peak oxygen consumption (VO2peak) between groups. There was a moderate effect (ES = 0.70) in favor of HIIT over SIT in maximal aerobic power (MAP) or maximal aerobic velocity (MAV). Conclusion: The results of the meta-analysis indicate that long-HIIT may be the optimal form of interval training to augment TT performance. Additional research that directly compares HIIT exercise differing in work-bout duration would strengthen these results and provide further insight into the mechanisms behind the observed benefits of long-HIIT.